Literasi Media Sosial Bagi Anak di SD Inpres Semangga 2 Distrik Semagga Kabupaten Merauke - Paul Adryani Moento; Alexander Phuk Tjilen; Fransin Kontu (Yayasan Perguruan Kampus, 2023)
Literacy skills encompass various aspects that contribute to an individual's ability to read, write, comprehend, and interact with texts and information. Literacy skills include the ability to read with comprehension, interpret and analyze written texts, write clearly and coherently, and communicate ideas and concepts effectively. The method applied in conducting this community service activity is through seminars for elementary school students. The topics covered in the seminars are divided into three main areas: Understanding Social Media, which refers to participants' understanding of the concept and functions of social media. The outcomes of this indicator include participants' ability to comprehend what social media is and how it operates. Next is Types of Social Media, where the indicator aims to ensure that participants have an understanding of various social media platforms. Participants identify and comprehend the differences between various types of social media and their respective uses. Lastly, the Benefits of Social Media cover participants' understanding of the advantages and benefits of using social media. Additionally, the Negative Impact of Social Media is also discussed to provide participants with an understanding of both the positive and negative aspects of social media.